PENGARUH PENGELUARAN PEMERINTAH TERHADAP KESEMPATAN KERJA DI SUMATERA UTARA - Munthe, Syafaruddin; Susilo, Eko Firman; Saprida (Ekomania, 2024)
This research aims to analyze the influence of exogenous variables on endogenous variables, namely government spending and employment opportunities. This type of research is quantitative analysis using secondary data with a time series from 1993 to 2022 obtained from the Central Statistics Agency (BPS) of North Sumatra and Bank Indonesia (BI). The data analysis technique in this research uses a simple regression analysis model. The results of this research show that exogenous variables have a significant effect on endogenous variables in the equation model. The Government Expenditure variable has a significant effect on the employment opportunity variable. For this reason, it is necessary to increase government spending, so that there can be a coherent increase in economic growth. With an increase in government spending, job opportunities will expand.